The clinical characteristics of pleural effusion in scrub typhus - Kim, Hyung Ho (BMC Infect Dis, 2016)
BACKGROUND: The aim of this study is to identify the factors associated with the occurrence of pleural effusion and to investigate the characteristics of pleural effusion in scrub typhus. METHODS: We conducted a retrospective analysis of the medical records of scrub typhus patients between January 2004 and December 2011 at Chosun University Hospital in South Korea. A total of 445 scrub typhus patients were divided into the following two groups: without (n = 352) or with pleural effusion (n = 93). The data of 18 scrub typhus patients who underwent thoracentesis were summarized. RESULTS: Multivariate analysis demonstrated that the following factors were associated with the occurrence of pleural effusion in scrub typhus: older age (odds ratio [OR] = 1.029, P = 0.037, confidence interval [CI] = 1.002–1.056); male gender (OR = 1.924, P = 0.020, CI = 1.109–3.340); presence of heart failure (OR = 2.628, P = 0.039, CI = 1.052–6.565); and lower albumin (OR = 0.107, P ≤ 0.001, CI = 0.058–0.196). Most pleural effusion presentations were bilateral (88 %) and small (91 %). The effusion had transudate characteristics in 7 patients and exudate characteristics in 11 patients based on Light’s criteria. CONCLUSIONS: This study provided the first data regarding the following four independent risk factors associated with the occurrence of pleural effusion: older age; male gender; the presence of heart failure; and lower albumin. The pleural effusion presentations in scrub typhus patients were bilateral and small in most cases, with transudate and/or exudate characteristics.